Living Inheritance and Innovative Expression of Intangible Cultural Heritage Quyi: A Case Study of Beilu Shandong Qinshu - Yang, Na (International Journal of Literature and Arts Studies, 2026)
This study comprehensively examines the living inheritance and innovative expression of Beilu Shandong Qinshu, a highly representative form of traditional Chinese Quyi, situated within the broader theoretical framework of intangible cultural heritage preservation. Using a rigorous qualitative case study approach, this research systematically explores the underlying transmission mechanisms, contemporary performance practices, and innovative transformations that characterize this traditional art form today. The in-depth analysis highlights how traditional apprenticeship-based inheritance models and active community participation fundamentally sustain cultural continuity across generations. Furthermore, it demonstrates how evolving performance contexts and novel expressive strategies reflect an ongoing, necessary adaptation to rapidly changing modern social environments. The empirical findings clearly indicate that Beilu Shandong Qinshu is successfully maintained through a highly dynamic interaction between historical tradition and contemporary innovation, where its enduring vitality depends heavily on continuous artistic reinterpretation rather than mere static preservation. At the same time, the strategic integration of modern performance spaces and advanced digital media significantly expands its communicative reach to younger audiences, though it simultaneously raises critical scholarly concerns regarding the maintenance of cultural authenticity and historical depth. Ultimately, this study significantly contributes to the academic understanding of living heritage by emphasizing adaptive mechanisms as the primary key to long-term cultural sustainability. It strongly suggests that a carefully balanced integration of traditional transmission methods, robust institutional support, and innovative digital dissemination is absolutely essential for the successful, long-term preservation of global intangible cultural heritage.